Development of Epoxy-OPEFB composites for shielding applications - Khamis, Ahmad (2019)
Microwave absorbers are widely used in applications to eliminate unwanted or stray radiated electro-magnetic signals which might interfere with a system’s operation. These absorbers are basically made up of a polymer matrix reinforced with a filler material which might be one element or more. Ferrite composites are widely used in the development of microwave absorbers. However, ferrites are expensive, corrosive, heavy, and non-biodegradable. This research focuses on using oil palm empty fruit bunch (OPEFB) fibres as a filler for microwave absorber with epoxy resin as the host matrix. OPEFB fibres have several advantages including biodegradability, low density, low cost, and better thermal properties. Also epoxy resin has various advantages such as good dimensional stability, high mechanical properties, ease of processing and curing, and moisture resistance. Epoxy-OPEFB composites were fabricated by varying the OPEFB percentages (0%, 5%, 10%, 15%, 20%, 25%, 30%, and 40%). OPEFB fillers of 300 μm size, epoxy resin and hardener were mixed and stirred to produce Epoxy-OPEFB composites using mini vortex mixer at 3000 rpm for 30 minutes at room temperature (25 °C). ). The total mass of each mixture was 12 g which then poured into two different flanges in order to use two different techniques of complex permittivity characterizations. The dielectric constant and loss factor are main parameters related to dielectric characteristics of a particular material, and directly associated to the absorbing characteristics. . The complex permittivity, transmission coefficient |S21|, reflection coefficient |S11|, power loss, reflection loss, and total shielding effectiveness (SE) were studied in the frequency range (8-12) GHz. Dielectric constant, loss factor, reflection and transmission coefficients of the composites were measured using rectangular waveguide (RWG) connected to vector network analyser (VNA) in the frequency range (8-12) GHz. Also an open ended coaxial probe (OECP) connected to a vector network analyser was utilized to measure the dielectric constant and loss factor of all composites at room temperature (25 °C). X-Ray diffraction was utilized to analyse the microstructure of the composites. The results show that the dielectric properties increased but |S11| and |S21| decreased by increasing OPEFB percentage in the composites. The complex permittivity was dependable on the OPEFB percentage of the composites, increasing OPEFB content in the composites caused an increment in the complex permittivity of Epoxy-OPEFB composites. Epoxy-OPEFB composites were found to have a very close dielectric constant and loss factor to ferrite-polymer composites. At 10 GHz, the dielectric constant and loss factor of the Epoxy- OPEFB composites were be between 2.8 to 3.35 and 0.14 to 0.29, respectively. In addition, results of |S11| and |S21| were used to determine the power loss, reflection loss and total shielding effectiveness of Epoxy-OPEFB composites. OPEFB had a strong influence on the shielding effectiveness, power loss and reflection loss which increased by increasing OPEFB percentage in the composites. The total shielding effectiveness values were found to be between 15.4 dB and 18.9 dB at 10 GHz. The calculations of the S-Parameters coefficients of the samples were carried out using Finite Element Method (FEM) technique by COMSOL software. The measured and calculated results of |S11| and |S21| were also investigated. The simulated and measured results of |S11| and |S21|were in a good agreement. Finally, the electric field distribution was visualized using Comsol software, it was found that the amplitude of electric field was strongly reduced after passing through Epoxy-OPEFB composites.